The Right to Self-Determination of Indigenous Peoples and the Proposed Nordic Sámi Convention: From Hopes Raised To Hopes Dashed? - Malaihollo, Medes (Cardinal Stefan Wyszynski University Publishing House, 2025)
During the first two decades of the twenty-first century, the right to self-determination of peoples in international law spread its wings. This is particularly true in the context of indigenous peoples. While much has already been written about the right to self-determination in international law, most of the legal literature has not reflected on the right to self-determination in the context of the legal developments of a Nordic Sámi Convention. In 2005, a first text was drafted which ambitiously presented a progressive self-determination model for the Sámi in Norway, Sweden, and Finland. However, in 2017 a new draft was proposed which reflected a different model. This article discusses how the right to self-determination of the Sámi operates under these two drafts. By comparing the self-determination models under the 2005 Draft and the 2017 Draft, it will become clear that much of the former has been streamlined under the latter, up to the point that the self-determination model under this new draft has been downgraded. At the same time, it becomes evident that the self-determination model under the 2005 Draft has serious value. Therefore, this article argues that the text of the 2005 Draft could still be used as a template for legal scholars and legal practitioners. Moreover, it could serve as a benchmark to inform and guide future policies and laws of any state that has an indigenous people residing in its territory.